2016
DOI: 10.3389/fpls.2016.00482
|View full text |Cite
|
Sign up to set email alerts
|

ALA Inhibits ABA-induced Stomatal Closure via Reducing H2O2 and Ca2+ Levels in Guard Cells

Abstract: 5-Aminolevulinic acid (ALA), a newly proved natural plant growth regulator, is well known to improve plant photosynthesis under both normal and stressful conditions. However, its underlying mechanism remains largely unknown. Stomatal closure is one of the major limiting factors for photosynthesis and abscisic acid (ABA) is the most important hormone in provoking stomatal closing. Here, we showed that ALA significantly inhibited ABA-induced stomatal closure using wild-type and ALA-overproducing transgenic Arabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
74
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(78 citation statements)
references
References 57 publications
4
74
0
Order By: Relevance
“…5-Aminolevulinic acid (ALA), a natural plant growth regulator, is known to improve plant photosynthesis under both normal (Hotta et al, 1997) and stressful conditions (Hotta et al, 1998; Nishihara et al, 2003; Wang et al, 2004; Liu et al, 2011; Zhang et al, 2012; Ali et al, 2013b). Recent investigations showed that ALA did not affect stomata development, but significantly inhibited stomatal closing (An et al, 2016a), indicating increasing stomatal aperture is an important mechanism of ALA-mediated improvement of photosynthesis. Most importantly, ALA improved plant drought tolerance simultaneously (An et al, 2016a), further suggesting its great application potential in agriculture and forestry.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…5-Aminolevulinic acid (ALA), a natural plant growth regulator, is known to improve plant photosynthesis under both normal (Hotta et al, 1997) and stressful conditions (Hotta et al, 1998; Nishihara et al, 2003; Wang et al, 2004; Liu et al, 2011; Zhang et al, 2012; Ali et al, 2013b). Recent investigations showed that ALA did not affect stomata development, but significantly inhibited stomatal closing (An et al, 2016a), indicating increasing stomatal aperture is an important mechanism of ALA-mediated improvement of photosynthesis. Most importantly, ALA improved plant drought tolerance simultaneously (An et al, 2016a), further suggesting its great application potential in agriculture and forestry.…”
Section: Introductionmentioning
confidence: 99%
“…Recent investigations showed that ALA did not affect stomata development, but significantly inhibited stomatal closing (An et al, 2016a), indicating increasing stomatal aperture is an important mechanism of ALA-mediated improvement of photosynthesis. Most importantly, ALA improved plant drought tolerance simultaneously (An et al, 2016a), further suggesting its great application potential in agriculture and forestry.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the increase in ABA level is a central player controlling downstream responses essential for adaptation to different stresses, especially drought (Davies et al, 2002 andGiuliani et al, 2005). These responses include changes in stomatal conductance (closure of stomata), osmolyte accumulation, gene expression, a reduced leaf canopy, deeper root growth and changes in root system architecture (Davies et al, 2002;Giuliani et al, 2005;Lee et al, 2013 andAn et al, 2016).…”
Section: Introductionmentioning
confidence: 99%